Serum Complement Activation by C4BP-IgM Fusion Protein Can Restore Susceptibility to Antibiotics in Neisseria gonorrhoeae - Bettoni, Serena; Maziarz, Karolina; Stone, M Rhia L; Blaskovich, Mark A T; Potempa, Jan; Bazzo, Maria Luiza; Unemo, Magnus; Ram, Sanjay; Blom, Anna M. (Frontiers in Immunology, 2021)
Neisseria gonorrhoeae is the etiological agent of gonorrhea, the second most common bacterial sexually transmitted infection worldwide. Reproductive sequelae of gonorrhea include infertility, ectopic pregnancy and chronic pelvic pain. Most antibiotics currently in clinical use have been rendered ineffective due to the rapid spread of antimicrobial resistance among gonococci. The developmental pipeline of new antibiotics is sparse and novel therapeutic approaches are urgently needed. Previously, we utilized the ability of N. gonorrhoeae to bind the complement inhibitor C4b-binding protein (C4BP) to evade killing by human complement to design a chimeric protein that linked the two N-terminal gonococcal binding domains of C4BP with the Fc domain of IgM. The resulting molecule, C4BP-IgM, enhanced complement-mediated killing of gonococci. Here we show that C4BP-IgM induced membrane perturbation through complement deposition and membrane attack complex pore insertion facilitates the access of antibiotics to their intracellular targets. Consequently, bacteria become more susceptible to killing by antibiotics. Remarkably, C4BP-IgM restored susceptibility to azithromycin of two azithromycin-resistant clinical gonococcal strains because of overexpression of the MtrC-MtrD-MtrE efflux pump. Our data show that complement activation can potentiate activity of antibiotics and suggest a role for C4BP-IgM as an adjuvant for antibiotic treatment of drug-resistant gonorrhea.